2017
DOI: 10.1126/sciadv.1700704
|View full text |Cite
|
Sign up to set email alerts
|

Giant Rashba splitting in 2D organic-inorganic halide perovskites measured by transient spectroscopies

Abstract: Transient and CW spectroscopies unravel giant Rashba splitting in 2D hybrid perovskite multilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
359
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(384 citation statements)
references
References 35 publications
24
359
1
Order By: Relevance
“…An analogous result is also obtained for c‐CH 3 NH 3 PbI 3 (Table ). These are in agreement with the results of similar other studies reported for c‐CH 3 NH 3 PbI 3 …”
Section: Computational Details Results and Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…An analogous result is also obtained for c‐CH 3 NH 3 PbI 3 (Table ). These are in agreement with the results of similar other studies reported for c‐CH 3 NH 3 PbI 3 …”
Section: Computational Details Results and Discussionsupporting
confidence: 94%
“…A number of recent studies indicate that spin‐orbit coupling (SOC) can split the doubly spin‐degenerate valence and conduction band edges in noncentrosymmetric compounds . As expected, and for the pseudocubic polymorphs such as those in (A) and (B) of Figure , the inversion symmetry is broken due to the displacements of the Pb atom from the center of the PbI 64 octahedra.…”
Section: Computational Details Results and Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Theoretical calculations based on DFT and experiments based on transient spectroscopy methods show that Rashba splitting occurs on a huge scale in 2D HOPs, where the energy splitting is (40 ± 5) meV and the Rashba parameter is (1.6 ± 0.1)eV Å. These findings also indicate that the 2D HOPs have a broad range of application prospects in spintronics, which is similar to the prospects of 3D HOPs. This research will pave the way toward new optoelectronic device designs based on 2D HOPs.…”
Section: Various Approaches To Construct Hop Spin‐related Optoelectromentioning
confidence: 55%
“…The valence band peak features a maximum 0.16 eV splitting depth, which occurs at k = 0.043 Å −1 . Another study in 2017 applied transient and steady‐state light modulation‐based spectral techniques to measure the exciton transitions and the free carrier absorption . The observed continuum band splitting reached ≈1.6 eV Å −1 in the 2D layered (C 6 H 5 C 2 H 4 NH 3 ) 2 PbI 4 perovskite, which was a considerably larger value when compared with previous work.…”
Section: Novel Spin‐related Physical Effects Arising From Hopsmentioning
confidence: 91%